Ecoproducts in the Dynamic Era of Digital Communication: A Neuromarketing Study of Users’ Emotional Reactions on Social Media - Simona Ščepková; Anna Zaušková (Communication Today, 2025)
In the present era, where social media have become a primary tool for interaction between brands and consumers, the importance of emotional reactions triggered by observing public comments is increasingly emphasised. This study analyses how these reactions shape the decision-making process when purchasing eco-friendly products. The aim of this study is to bridge the gap in the analysis of emotional reactions from social media users who are exposed to various unofficial information published on social media while gathering information about eco-products, which can significantly influence their purchasing decisions. The objective is to examine, compare, and evaluate how positive and negative sentiment in user comments affects the perception and value of eco-products amongst other social media users. The findings indicate that posts with positive comments foster increased engagement and a favourable perception of products, while negative comments lead to doubt and frustration. In the neuromarketing experiment, we found that 81.8% of respondents considered the visual design of the eco-product and the ecological brand message attractive, with 63.6% reporting that negative social media comments had a significant impact on their perception of the brand. These results support the hypothesis that emotional reactions to comments are a strong factor in consumer decision-making, suggesting that positive reviews may serve as social proof, while negative comments can cause cognitive dissonance. Through this study, we aim to contribute to a deeper understanding of the dynamics between emotional reactions and the perception of eco-products in the digital communication era, which has significant implications for the marketing strategies of ecological brands.